Usefulness of the English language teaching textbook evaluation checklist - Nimehchisalem, Vahid; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2013)
Textbook evaluation checklists are instruments that help teachers or programme developer sevaluate teaching materials before or after using them. This paper presents one of the phases of a project that involved the survey of a group of evaluators’ (n=82) views on the usefulness of a newly developed checklist. The questionnaire used was a modified version of an instrument developed to evaluate the usefulness of a writing scale (Nimehchisalem, 2010). Based on the results, the checklist indicates high to very high levels of usefulness. The findings are expected to be very helpful for researchers who may intend to test similar instruments.